Sosialisasi Program Kerja Yatim Mandiri melalui Safari Dongeng pada Anak Sekolah di Kabupaten Kediri - Kusumawardhany, Sayekti Indah; Mu’jizati, Faaidatul; Agustina, Andhin Rosita Wahyu; Hidayah, Ariesya Afrillia Nur; Aima, Devi Nur (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The National Zakat Collection Institution (LAZNAS) Yatim Mandiri is a social organization committed to improving the welfare of orphans and the poor through ZISWAF funds and other halal funding sources. One of its flagship programs is Safari Dongeng Karakter, an initiative aimed at providing character education to elementary and secondary school students through inspirational and educational stories. This program aims to broaden students' horizons and strengthen the relationship between Yatim Mandiri and the community, schools, and professional storytellers. By packaging stories based on Islamic values ​​and exemplary behavior, Safari Dongeng Karakter creates a fun and memorable learning experience for participants. The success of this program is reflected in the enthusiasm of students and the support of various parties in the sustainability of activities. Yatim Mandiri continues to innovate to expand the benefits of this program, providing a wider positive impact for orphans and the poor.